Clinical outcome and subsequent sequelae of cement extravasation after percutaneous kyphoplasty and vertebroplasty: a comparative review. (July 2018) - Semaan, Hassan; Obri, Tawfik; Bazerbashi, Mohamad; Paull, Daniel; Liu, Xiaochen; Sarrouj, Marah; Elgafy, Hossein
Background: Injection of cement during vertebroplasty and kyphoplasty can leak into surrounding structures and could be symptomatic. Purpose: To identify the sites and incidence of cement extravasation after kyphoplasty and vertebroplasty, and to evaluate their impacts on clinical outcomes. Material and Methods: A retrospective review of 316 patients treated with kyphoplasty and vertebroplasty; 411 cases were included (223 kyphoplasty and 188 vertebroplasty). Cement extravasation was evaluated postoperatively by computed tomography (CT) scan of the spine. Clinical outcomes were assessed by visual analog scale (VAS) and Oswestry Disability Index (ODI). Results: There was a statistically significant difference in the incidence rate of cement extravasation between vertebroplasty and kyphoplasty groups ( P  < 0.04). The most common site of cement extravasation was in paravertebral soft tissues for vertebroplasty (n = 33, 40.7%) and for kyphoplasty (n = 30, 30%). In the subgroup where cement leaked into the intradiscal space, adjacent vertebral body fractures occurred in 3/26 vertebrae (11.5%) in the vertebroplasty group and in 2/18 vertebrae (11.1%) in the kyphoplasty group. Both groups showed a statistically significant decrease in both VAS ( P  < 0.001) and ODI scores ( P  < 0.001). There was no significantly difference in patient satisfaction between those who had cement extravasation and those who did not, in both groups. Conclusion: Kyphoplasty has an advantage in terms of less risk of cement extravasation. However, this factor did not reflect on subsequent sequelae or final clinical outcomes. This study did not find a distinct correlation between intradiscal cement extravasation and increased risk of adjacent vertebral fractures.